Macroeconomic determinants of malaysian stock market / Nurul Asiah Ismail - Ismail, Nurul Asiah (Faculty of Business and Management, 2015)
This paper examines the macroeconomic determinants of stock market development using a time series data of 36 emerging economies for 2005 to 2013. The paper finds that macroeconomic factors such as money supply, reserve, interest rate industrial production and exchange rate are important determinants of stock market development in emerging market countries. This result suggests that the resolution of political risk can be an important factor in the development of emerging stock markets. The analysis also shows the factors identified above as determining stock market development in emerging economies can also explain the development of the stock market in Malaysia.